Iron age burial mounds as refugia for steppe specialist plants and invertebrates – case study from the Zsolca mounds (NE Hungary) - Tóth, Csaba Albert; Deák, Balázs; Nyilas, István; Bertalan, László; Valkó, Orsolya; Novák, Tibor József (Hacquetia, 2025)
Prehistoric mounds of the Great Hungarian Plain often function as refuges for relic loess steppe vegetation and their associated fauna. The Zsolca mounds are a typical example of kurgans acting as refuges, and even though they are surrounded by agricultural land, they harbour a species rich loess grassland with an area of 0.8 ha. With a detailed field survey of their geomorphology, soil, flora and fauna, we describe the most relevant attributes of the mounds regarding their maintenance as valuable grassland habitats. We recorded 104 vascular plant species, including seven species that are protected in Hungary and two species (Echium russicum and Pulsatilla grandis) listed in the IUCN Red List and the Habitats Directive. The negative effect of the surrounding cropland was detectable in a three-metre wide zone next to the mound edge, where the naturalness of the vegetation was lower, and the frequency of weeds, ruderal species and crop plants was higher than in the central zone. The ancient man-made mounds harboured dry and warm habitats on the southern slope, while the northern slopes had higher biodiversity, due to the balanced water supplies. Both microhabitats had different assemblages of grounddwelling invertebrates.